2021
DOI: 10.1111/tpj.15311
|View full text |Cite
|
Sign up to set email alerts
|

Boron deficiency‐induced root growth inhibition is mediated by brassinosteroid signalling regulation in Arabidopsis

Abstract: Summary Brassinosteroids (BRs) are pivotal phytohormones involved in the control of root development. Boron (B) is an essential micronutrient for plants, and root growth is rapidly inhibited under B deficiency conditions. However, the mechanisms underlying this inhibition are still unclear. Here, we identified BR‐related processes underlying B deficiency at the physiological, genetic, molecular/cell biological and transcriptomic levels and found strong evidence that B deficiency can affect BR biosynthesis and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 77 publications
2
18
0
Order By: Relevance
“…Therefore, defects in cell division could be an early response upon boron deficiency in maize. These findings are supported by recent evidence from Arabidopsis RAMs, where cell division was found to be an early target of the boron deficiency response (Poza‐Viejo et al, 2018; Zhang et al, 2020). Our findings suggested that early boron responses are at least in part conserved between the Arabidopsis RAM and the maize tassel meristem.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Therefore, defects in cell division could be an early response upon boron deficiency in maize. These findings are supported by recent evidence from Arabidopsis RAMs, where cell division was found to be an early target of the boron deficiency response (Poza‐Viejo et al, 2018; Zhang et al, 2020). Our findings suggested that early boron responses are at least in part conserved between the Arabidopsis RAM and the maize tassel meristem.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, defects in cell division could be an early response upon boron deficiency in maize. These findings are supported by recent evidence from Arabidopsis RAMs, where cell division was found to be an early target of the boron deficiency response(Poza-Viejo et al, 2018;Zhang et al, 2020). Our findings suggested that early boron responses are at least in part conserved between the Arabidopsis RAM and the maize tassel meristem.Reductions in cell division in the SAM were correlated with reduced WUS levels in Arabidopsis(Yadav et al, 2010) and in boron deficient roots cell division defects precede the loss of the quiescent center (QC) (as judged by the loss of the QC marker QC46:GUS) (Poza-Viejo…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Under B toxicity, a substantial decrease in chlorophyll content (Chen et al, 2014) and structural changes in thylakoid membranes suggest that RERs may be involved in the development of B toxicity symptoms in plants. Surprisingly, the primary root growth is inhibited under B deficiency due to the down-regulation of BR biosynthesis genes and reduction in the active BR levels in Arabidopsis roots (Zhang et al 2021). BRs are also responsible for the inhibition of shoot growth under B deficiency (Eggert and von Wirén, 2017).…”
Section: Orthologs Of Abi954051 In Arabidopsis Encode For Fasciclin-likementioning
confidence: 99%